2023
DOI: 10.1001/jama.2023.7232
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Harassment, Cyber Incivility, and Climate in Academic Medicine

Abstract: ImportanceThe culture of academic medicine may foster mistreatment that disproportionately affects individuals who have been marginalized within a given society (minoritized groups) and compromises workforce vitality. Existing research has been limited by a lack of comprehensive, validated measures, low response rates, and narrow samples as well as comparisons limited to the binary gender categories of male or female assigned at birth (cisgender).ObjectiveTo evaluate academic medical culture, faculty mental he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Of 1430 individuals surveyed, 915 responded (64.0%); respondents did not differ significantly from nonrespondents by gender . The analytic sample was restricted to respondents remaining in academia (830 [90.7%]) and, for gender comparisons, to those identifying as men (422 [50.8%]) or women (385 [46.4%]).…”
Section: Resultsmentioning
confidence: 99%
“…Of 1430 individuals surveyed, 915 responded (64.0%); respondents did not differ significantly from nonrespondents by gender . The analytic sample was restricted to respondents remaining in academia (830 [90.7%]) and, for gender comparisons, to those identifying as men (422 [50.8%]) or women (385 [46.4%]).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, prior research has shown that small differences between groups, even with small effect sizes, can accumulate over time and have substantial influence on real world outcomes . Moreover, the size of differences between groups are similar to results found in other climate surveys used by the AAMC and in prior national studies . Future studies of the tool will examine how differences in tool scores influence disparities in consequential student outcomes in the learning environment, including attrition, successful placement into graduate medical education, burnout, and the receipt of academic awards.…”
Section: Discussionmentioning
confidence: 99%
“…The data reported here are part of an ongoing longitudinal study of clinician-scientists who received National Institutes of Health (NIH) K08 or K23 career development awards between 2006 and 2009 . We surveyed individuals 3 times, most recently in 2021 …”
Section: Methodsmentioning
confidence: 99%